Reseña: "Debating and defining borders: Philosophical and theoretical perspectives" (2020), de Anthony Cooper y Søren Tinning - Andrea Itzel Padilla (Universitat Autònoma de Barcelona, 2021)
Reseña: Debating and defining borders: Philosophical and theoretical perspectives (2020), de Anthony Cooper y Søren Tinning